What is a sustainable healthy diet? A discussion paper - Garnett, Tara; Appleby, M.C.; Balmford, A.; Bateman, I.J.; Benton, Tim G.; Bloomer, P.; Burlingame, B.; Dawkins, M.; Dolan, L.; Fraser, D.; Herrero, Mario; Hoffmann, I.; et al. (Food Climate Research Network, 2014)
The food system today is destroying the environment upon which future food production depends. While the food system generates enough food energy for our population of over 7 billion it does not deliver adequate and affordable nutrition for all. About half the global population is inadequately or inappropriately nourished. Without action, these problems are set to become acute. As our global population grows, urbanises and becomes wealthier, it is demanding more resource intensive, energy rich foods. What, and how much we eat directly affects what, and how much is produced. We therefore need to consume more „sustainable diets‟ – diets that have lower environmental impacts, and are healthier. But what does such a diet look like? Can health, environmental sustainability, and all the other goals we have for our food system really be reconciled, or will there be trade offs?